Knowledge is Power: Experts as a Strategic Group - Hans-Dieter Evers and Solvay Gerke
The theory of strategic groups assumes that strategic groups are built when new resources become available as a result of social change. This paper examines the extent to which the process of globalization creates new chances for the acquisition of resources, which also leads to the creation of global strategic groups. Knowledge is identified as one of such strategic resources that makes it possible for strategic groups to be formed. This paper attempts to prove how experts, in particular development experts, form such a strategic group which applies knowledge gained from experience and action strategies to obtain resources for themselves and for their projects